Influence of Operating Frequency and Ambient Temperature on Reciprocating Magnetic Cooling - Wang Qi; Liu Bin; Chen Aiqiang; Li Peng (Zhileng xuebao)
To analyze the influence of different working frequencies and room temperatures on the cooling span of a reciprocating room-temperature magnetic refrigeration system, a setup for such a system was designed with granular Gd (particle size: 0.3-0.5 mm) as the magnetic working mass. The cooling temperature of the reciprocating room-temperature magnetic refrigeration system was then analyzed, combined with the heat transfer characteristics in the active cooler during the experiment. A 1.5 T permanent magnet field strength was maintained, and the changes in the cold- and hot-end temperatures of the cold accumulator were measured at different operating frequencies (0.07, 0.12, 0.16, 0.19, 0.22 Hz) and room temperatures (14.5, 15.9, 16.7, 18.1 ℃). The results show that, when the operating frequency is 0.22 Hz, the maximum refrigeration temperature span of the system is 12.8 ℃. Further, when the Gd temperature is lower than the Curie temperature of 20 ℃, the room temperature has no effect on the cooling capacity of the magnetic refrigeration system over a finite time period.